In search of linguistic subtlety, or possible ways of studying linguistic finesse - Makarewicz, Renata (Papers in Linguistics, 2025)
The aim of this article is to present a method for studying linguistic finesse. The author draws on Michael Halliday’s functional grammar, James R. Martin and David Rose’s systemic functional discourse analysis (SFDA), and traditional stylistic studies. The text includes the author’s own compilations of examples of linguistic finesse (terminology from the field of stylistics) in various literary and journalistic genres. It is proposed to use the technique of competent judges to determine the conditions that must be met in order to establish whether linguistic finesse occurs in a text. This technique is rarely used nowadays, as corpus and statistical research are more commonly employed. Identifying repeatable criteria for the use and interpretation of finesse as a linguistic feature requires competent judges to assess it. It is only then that the obtained results can be used as the basis for what the author deems an appropriate research method: systemic functional discourse analysis (SFDA).